A comparative analysis of chemistry curriculum for lower secondary education in the Czech Republic, Poland, Slovenia and Estonia - Stratilová Urválková, Eva; Teplá, Milada; Janoušková, Svatava (Scientia in educatione, 2019)
This article presents an analysis based on the principles of (international) comparative pedagogy focusing on the study of the similarities and differences in subject-specific competences, educational content, and teaching strategies and methods. The analysis focuses on the field of chemistry, specifically the intended curriculum of the abovementioned countries for the level of lower secondary education. Three parameters were monitored and compared: the number of hours allocated for the teaching of chemistry, of all science subjects from the 6th to 9th grades, the educational content of the subject of chemistry and the teaching strategies discussed and/or recommended for the teaching of natural sciences. Analysis has shown that chemistry is taught for the same length of time, but chemistry topics in Slovenia and Estonia are also taught within the subject Natural Sciences in the 7th grade. The expected outcomes are comparable in all countries, but Czech outcomes are grouped into broad topic areas with few outcomes. The expected outcomes from other countries are specified in much more detail. The recommended teaching methods are most closely described in the Slovenian curriculum, which also contains extensive didactic recommendations for individual subjects.